A programmable resonator based on a shunt-electro-mechanical diaphragm. (1st September 2022) - Zhang, Yumin; Wu, Keming; Zhang, Xingyu; Liu, Xiang; Huang, Lixi
Highlights: A programmable resonator called shunted electromechanical resonator (SEMR) is proposed and theoretical analyzed, which is proved in experiments The resonance frequency, ideally, can be programed in the frequency range of (0 ∞) as long as the resistance of the pre-design shunt circuits approaching zero The programing process of the mechanical resonance only requires coding the supplied DC voltages to the MOSFET switches The frequency range of tuning is much broader than existing technology Abstract: As the most classical device, Helmholtz resonator (HR) is simple and robust leading its widely using in control of sound wave. However, it performs only in the vicinity of its resonant frequency which restrains its application scope. Method to extending its effective frequency range is long-time sought by various techniques. This study introduces a programmable resonator whose resonance frequency is determined by a programed voltage states. In this resonator, the mass inducing neck is replaced by the diaphragm of a moving-coil loudspeaker which is shunted by an analog circuit. The acoustic impedance of the diaphragm, hence the resonance frequency, is dominated by the circuit through the electromechanical coupling induced by a moving-coil in a DC magnetic field. To program the resonance, a multiple branches programmable circuit is designed. The connecting state of each branch of circuit is coded by a low-voltage supplied to a metal-oxide-semiconductor field-effect transistor (MOSFET) switch cascading the branch. By programming the voltages, the resonance frequency is successfully coded. Both down-tuning and up-tuning of the resonance frequency is realized in impedance tube experiment which agrees well with the lumped parameter model developed in this work. The tuning range is up to 1 octave in experiments and infinite large in theory if superconducting coil is used. Graphical abstract: Image, graphical abstract